Epidemiological characteristics of infectious hematopoietic necrosis virus (IHNV): a review. (December 2016) - Dixon, Peter; Paley, Richard; Alegria-Moran, Raul; Oidtmann, Birgit
Abstract Infectious hematopoietic necrosis virus (IHNV, Rhabdoviridae ), is the causative agent of infectious hematopoietic necrosis (IHN), a disease notifiable to the World Organisation for Animal Health, and various countries and trading areas (including the European Union). IHNV is an economically important pathogen causing clinical disease and mortalities in a wide variety of salmonid species, including the main salmonid species produced in aquaculture, Atlantic salmon (Salmo salar ) and rainbow trout (Oncorhynchus mykiss ). We reviewed the scientific literature on IHNV on a range of topics, including geographic distribution; host range; conditions required for infection and clinical disease; minimum infectious dose; subclinical infection; shedding of virus by infected fish; transmission via eggs; diagnostic tests; pathogen load and survival of IHNV in host tissues. This information is required for a range of purposes including import risk assessments; parameterisation of disease models; for surveillance planning; and evaluation of the chances of eradication of the pathogen to name just a few. The review focuses on issues that are of relevance for the European context, but many of the data summarised have relevance to IHN globally. Examples for application of the information is presented and data gaps highlighted.